Human stefin B normal and patho-physiological role: molecular and cellular aspects of amyloid-type aggregation of certain EPM1 mutants - Polajnar, Mira; Čeru, Slavko; Kopitar-Jerala, Nataša; Žerovnik, Eva (Frontiers in Molecular Neuroscience, 2012)
Epilepsies are characterised by abnormal electrophysiological activity of the brain. Among various types of inherited epilepsies different epilepsy syndromes, among them progressive myoclonus epilepsies with features of ataxia and neurodegeneration, are counted. The progressive myoclonus epilepsy of type 1 (EPM1), also known as Unverricht-Lundborg disease presents with features of cerebellar atrophy and increased oxidative stress. It has been found that EPM1 is caused by mutations in human cystatin B gene (human stefin B). We first describe the role of protein aggregation in other neurodegenerative conditions. Protein aggregates appear intraneurally but are also excreted, such as is the case with senile plaques of amyloid- β (Aβ) that accumulate in the brain parenchyma and vessel walls. A common characteristic of such diseases is the change of the protein conformation towards β secondary structure that accounts for the strong tendency of such proteins to aggregate and form amyloid fibrils. Second, we describe the patho-physiology of EPM1 and the normal and aberrant roles of stefin B in a mouse model of the disease. Furthermore, we discuss how the increased protein aggregation observed with some of the mutants of human stefin B may relate to the neurodegeneration that occurs in rare EPM1 patients. Our hypothesis (Ceru et al., 2005) states that some of the EPM1 mutants of human stefin B may undergo aggregation in neural cells, thus gaining additional toxic function (apart from loss of normal function). Our in vitro experiments thus far have confirmed that 4 mutants undergo increased aggregation relative to the wild-type protein. It has been shown that the R68X mutant forms amyloid-fibrils very rapidly, even at neutral pH and forms perinuclear inclusions, whereas the G4R mutant exhibits a prolonged lag phase, during which the toxic prefibrillar aggregates accumulate and are scattered more diffusely over the cytoplasm. Initial experiments on the G50E and Q71P missense